Fort Reno and the Indian Territory Frontier - Hoig, Stan (Book collections on Project MUSE., 2000)
"The story of Fort Reno, as detailed here by Stan Hoig, touches on several of the most important topics of nineteenth-century Western history: the great cattle drives, Indian pacification and the Plains Wars, railroads, white settlement, and the Oklahoma land rushes. Hoig deals not only with Fort Reno, but also with Darlington agency, the Chisolm Trail, and trading activities in Indian Territory from 1874 to approximately 1900. The author includes maps, photographs, and illustrations to enchance the narrative and guide the reader, like a scout, through a time of treacherous but fascinating events in the Old West."--Jacket.